2014
DOI: 10.1111/bjet.12166
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of online instructional videos in the acquisition and demonstration of cognitive, affective and psychomotor rehabilitation skills

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 26 publications
3
46
1
2
Order By: Relevance
“…Their motivation and reasons for using online streaming media services in education was also significantly positive among all subgroups, with a high mean score (M = 4.32, and SD = 0.32). These findings are consistent with the results of earlier studies conducted within the previous 10 years in several geographic regions and a variety of disciplines (Boster, Meyer, Roberto, Inge, & Strom, 2006;Cascaval et al, 2008;Chang, 2004;Cooper & Higgins, 2014;Fredriksen, 2015;Green et al, 2003;Hartsell & Yuen, 2006;Leijen et al, 2009;Mardis, 2009;Sowan & Abu Idhail, 2014;Trier, 2007a;Trier, 2007b;Wang et al, 2010;Yunus et al, 2006). The results also confirm the hypotheses presented earlier in this paper.…”
Section: Discussionsupporting
confidence: 92%
“…Their motivation and reasons for using online streaming media services in education was also significantly positive among all subgroups, with a high mean score (M = 4.32, and SD = 0.32). These findings are consistent with the results of earlier studies conducted within the previous 10 years in several geographic regions and a variety of disciplines (Boster, Meyer, Roberto, Inge, & Strom, 2006;Cascaval et al, 2008;Chang, 2004;Cooper & Higgins, 2014;Fredriksen, 2015;Green et al, 2003;Hartsell & Yuen, 2006;Leijen et al, 2009;Mardis, 2009;Sowan & Abu Idhail, 2014;Trier, 2007a;Trier, 2007b;Wang et al, 2010;Yunus et al, 2006). The results also confirm the hypotheses presented earlier in this paper.…”
Section: Discussionsupporting
confidence: 92%
“…7,8 The use of instructional videos in addition to traditional classroom instructions has proven to be effective in developing cognitive skills, enhancing psychomotor skills and improving knowledge retention. 9 Additionally, video recordings ensure consistency of message and content when multiple learning sessions are required to accommodate student numbers. This reduces fatigue for the teaching staff and provides didactic rigour.…”
mentioning
confidence: 99%
“…For example, in a study of iPad use in higher education, Nguyen, Barton and Nguyen (2015) found that iPads enhanced the learning experience of students but did not lead to improved learning outcomes. Cooper and Higgins (2015) found that they could not conclude that online instructional videos for undergraduate students improved learning and teaching. Tsekleves, Cosmas, and Aggoun (2016) examined the barriers to the use of serious games in higher education and concluded that it was unclear how games could be incorporated within formal education systems.…”
Section: Literature Reviewmentioning
confidence: 98%